2018
DOI: 10.1016/j.celrep.2018.01.044
|View full text |Cite|
|
Sign up to set email alerts
|

Supraphysiologic Administration of GDF11 Induces Cachexia in Part by Upregulating GDF15

Abstract: The age-related effects of GDF11 have been a subject of controversy. Here, we find that elevated GDF11 causes signs of cachexia in mice: reduced food intake, body weight, and muscle mass. GDF11 also elicited a significant elevation in plasma Activin A, previously shown to contribute to the loss of skeletal muscle. The effects of GDF11 on skeletal muscle could be reversed by administration of antibodies to the Activin type II receptors. In addition to the effects on muscle, GDF11 increased plasma GDF15, an anor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 33 publications
2
50
1
Order By: Relevance
“…A recent report suggested that very high levels or supraphysiological overexpression of GDF11 promotes activin A mediated cachexia and directly invokes an increase in circulating levels of the TGFβ ligand, GDF15 14 , also known macrophage inhibitory cytokine-1 (MIC1). This study further suggested that elevated GDF15 acts as an appetite suppressant, resulting in weight loss 14 . As it is known that a reduction in body weight can have n = 9 mice/treatment) and aged (E, n = 6-8 mice/treatment; G, 9-10 mice/treatment) mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report suggested that very high levels or supraphysiological overexpression of GDF11 promotes activin A mediated cachexia and directly invokes an increase in circulating levels of the TGFβ ligand, GDF15 14 , also known macrophage inhibitory cytokine-1 (MIC1). This study further suggested that elevated GDF15 acts as an appetite suppressant, resulting in weight loss 14 . As it is known that a reduction in body weight can have n = 9 mice/treatment) and aged (E, n = 6-8 mice/treatment; G, 9-10 mice/treatment) mice.…”
Section: Resultsmentioning
confidence: 99%
“…These observations thus raise the possibility that GDF11 may participate in appetite regulation. (2020) 10:4561 | https://doi.org/10.1038/s41598-020-61443-y www.nature.com/scientificreports www.nature.com/scientificreports/ A recent report suggested that GDF11 can stimulate the production of GDF15, which then acts as an appetite suppressant 14 . We tested the plasma of young and aged mice following the conclusion of the daily 0.5 mg/kg ligand dosing regimen, and we did not find any differences in circulating levels of GDF15 among the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIC-1/GDF15 mRNA expression and/or serum levels are elevated by drug classes such as cyclooxygenase inhibitors (Baek et al, 2001), many organic compounds isolated from natural products (Bottone et al, 2002;Baek et al, 2004a), the anti-diabetic drug metformin (Gerstein et al, 2017), anticancer therapies including chemotherapy and ionizing irradiation (Kis et al, 2006;Okazaki et al, 2006;Moritake et al, 2012;Tucker et al, 2014), the cytokine GDF11 (Jones et al, 2018), and tissue injury (Schober et al, 2001;Hsiao et al, 2000;Koniaris, 2003), strenuous exercise (Tchou et al, 2009;Galliera et al, 2014;Kleinert et al, 2018), cardiac (Kempf et al, 2007b;Stiermaier et al, 2014), and renal failure (Johnen et al, 2007;Breit et al, 2012;Ho et al, 2013), chronic liver disease (Liu et al, 2015;Lee et al, 2017), chronic inflammatory diseases like rheumatoid arthritis (Brown et al, 2007;Tanrıkulu et al, 2017), scleroderma (Yanaba et al, 2012;Gamal et al, 2017), and Behcet's syndrome (Sarıyıldız et al, 2016). Because MIC-1/GDF15 serum levels were elevated in a wide range of malignancies, studies of disease-associated expression of MIC-1/ GDF15 initially focused on the cancer area.…”
Section: Mic-1/gdf15 Expressionmentioning
confidence: 99%
“…Etiologically, CAC is driven by various metabolic abnormalities besides anorexia, including elevated energy expenditure, excess catabolism and inflammation . Multifactorial pathogeneses of CAC necessitate combination therapies and the development of novel therapeutics to improve the quality of life of patients and their tolerance to cancer therapy . Studying the potential mechanisms of CAC could provide clues on novel therapeutics for CAC patients.…”
Section: Introductionmentioning
confidence: 99%